#TITLE_ALTERNATIVE# - ARIF (NIM 151 04 068), NAZIH
Ocean Tidal Loading (OTL) is the dynamics of the earth's crust usually found on the coastline which is caused by fluctuations of the sea level which relate to tides. OTL has an impact toward the result of GPS measurement, such as the vertical and horizontal positions, especially on GPS observation points near the coastline. In this Final Report, a study will be done regarding the influence of OTL toward GPS measurements. GPS observation points examined are categorized into three variations, which is spatial, baseline and processing time interval. Spatial variations are inlands far from the sea, inlands close to the sea and points that cross straits or islands. Baseline length variations are medium, long, and very long baselines. Processing time intervals are 6 hours, 12 hours, and 24 hours. The observation points are continued GPS fixed stations. In data processing of continued GPS, BERNESE Software V.5 is used with static method and a radial baseline. To achieve an impact pattern from the OTL, process results with and without global tide correction model (FES04 and GOT 00.2) is compared, continued with an analysis of processing time intervals, baseline length, and observation location. OTL creates a big impact on baselines categorized as long (>300 km) and very long (>2000km), and also observation points close to oceans and islands. Influence of OTL can be concluded based on processing time intervals of 24 hours, which is assumed to have less errors and biases other than the OTL. The effect of OTL happens on easting, northing and up components, whereas impacts on up and easting components are larger than northing components.